Enhancing work engagement: The roles of psychological capital, authentic leadership, and work empowerment. Issue 8 (7th November 2016) - Joo, Baek-Kyoo; Lim, Doo Hun; Kim, Sewon
Abstract : Purpose: The purpose of this paper is to examine the influences of psychological capital (PsyCap) on work engagement. It also investigated the role of work empowerment as a mediator and authentic leadership as a moderator. Design/methodology/approach: Data were collected from 599 knowledge workers in a Korean conglomerate. For statistical analysis, the authors conducted the confirmatory factor analysis, reliability and correlation analysis, and hierarchical multiple regression analyses. Findings: The results suggest that employees were highly engaged when they had higher PsyCap. Work empowerment partially mediated the relationship between PsyCap and work engagement. While authentic leadership was found to moderate the relationship between PsyCap and work empowerment, the proposed moderation effect of authentic leadership on the relationship between PsyCap and work engagement turned out to be non-significant. Research limitations/implications: The sample of this study was focused on knowledge workers in the Korean private sector who are mostly male junior or middle managers. This empirical study relied on a cross-sectional survey method. As the results of exploratory and confirmatory factor analyses, however, common method variance was found not to be of great concern. Practical implications: HR and OD practitioners can help employees develop more positive attitudes about their work. It is also important to improve employees' empowerment and engagement level not only by helping employees enhance the level of PsyCap, but also by job enrichment and by developing authentic and supportive leadership. Originality/value: The contributions of this study to theory lie in the fact that it: took an integrative approach encompassing both personal and contextual factors; introduced relatively new constructs in empowerment and engagement research: PsyCap and authentic leadership; was an international study, based on Korean cultural context.